Analisis Implementasi Prinsip Good Islamic Pension Fund Governance (GIPFG) Dalam Tata Kelola Dana Pensiun POS (DAPENPOS) - Sani, Sri Aderafika; Zainarti, Zainarti; Harahap, Rahmat Daim (LPPM Universitas Labuhanbatu, 2023)
In the development of sharia pension funds, important actions are needed to strengthen the institution. The most basic action is to uphold the Principles of Good Islamic Pension Fund Governance (GIPFG). This study aims to find out how the management of the Pos Indonesia Pension Fund is in accordance with the principles of Good Islamic Pension Fund Governance, and what are the obstacles in implementing the GIPFG Principles. This research is a qualitative research. Research subjects in this study were taken by purposive sampling, namely the HR department and the Head of Secretariat and General Affairs. The results of this study indicate that according to the guidelines for the implementation of governance of the Pos Indonesia pension fund Number: KD 161/DIRUT/1217 the management of the Pos Indonesia Pension Fund has not been managed in sharia or not in accordance with the Principles of Good Islamic Pension Fund Governance. Dapenpos' obstacles in implementing the Principles of Good Islamic Pension Fund Governance are because this company is not an Islamic company, there is no role of the Sharia Supervisory Board (DPS) which regulates and oversees the management of Postal pension funds, regulatory restrictions on Islamic pension funds, restrictions on Islamic investment instruments, HR restrictions, the unclear management model of Islamic pension funds, as well as the lack of understanding of Islamic pension funds. Currently the management of Pos Indonesia pension funds is guided by the Financial Services Authority Regulation Number 16/POJK.05/2016 concerning Pension Fund Governance which carries out the principles of Good Pension Fund Governance (GPFG), namely Transparency, Accountability, Responsibility, Independence, and Justice.